Cross-group friendships, the irony of harmony, and the social construction of "discrimination". Issue 7 (27th May 2020) - Greenland, Katy; Augoustinos, Martha; Andreouli, Eleni; Taulke-Johnson, Richard
ABSTRACT: Cross-group friendships are often assumed to be a panacea to intergroup conflict. However, the irony of harmony hypothesis suggests that friendships can have negative consequences for collective action and social change. We complement this research with accounts of cross-group friendship, using interviews and focus groups with minority (African-Caribbean and/ or gay) and majority (White and/ or heterosexual) participants ( n = 54). Participants repeatedly deployed "friendship" as an idealized category such that what happened within friendship could not be constructed as discrimination. Majority participants said that anything that happened within friendship could only be a mistake/ misunderstanding that would be easy to rectify. Minority participants struggled to reconcile the category entitlements of friendship with the problematic experiences that they described, but constructing such experiences as "discrimination" presented practical, moral, and rhetorical difficulties. Harmonious cross-group friendship may therefore require that minorities become tolerant to discrimination, while simultaneously enabling majorities to warrant (ill-informed) claims.